DEFERRED STATISTICAL CONVERGENCE ON TIME SCALES - Cinar, Muhammed; Yilmaz, Emrah; Et, Mikail (Editura Acad Romane, 2021)
In this study, we introduce deferred statistical convergence and strongly deferred Cesaro summability on an arbitrary time scale. Moreover, we examine some relationship between deferred statistical convergence and strongly deferred Cesaro summability on time scales.
Keywords: statistical convergence; time scales; Cesaro summability